Managing event sponsorships effectively: case study on Celcom (M) Bhd / Mohd Ilham Harun - Harun, Mohd Ilham (Faculty of Business and Management, 2009)
As a telecommunication company, customers are the most importance key in the Celcom Mobile Sdn Bhd as the business nature. The satisfaction of the customer will ensure the business growth and the strengths to compete with other rivals in the market. Based on this believe, this research was conducted which is to know whether Celcom Mobile Sdn Bhd is successful in managing event sponsorships effectively to corporate customer by loyalty program of Celcom. For the Chapter 1 explains the background and the introduction of the research. Chapter 2 is explaining the literature review to support the research, while Chapter 3 explores the research methodology and the sampling technique. In Chapter 4 will discuss the finding and interpretation of data and the last chapter is Chapter 5 will share the conclusion and the recommendation towards the finding. The finding shows the Celcom will get the good opportunity by make a loyalty programs. Manage event due to Celcom too conscious about customer needs because that services can give goodwill and long term benefits to Celcom but the planning of events usually give bad impression to Celcom Mobile Sdn. Bhd. in order to achieve good services for corporate customer before implementing the process of managing event. Celcom need to take an action to overcome the dissatisfaction among the organizer, agencies and Enterprise to avoid of mistaken on manage event sponsorships effectively.